SEASONAL CHANGE OF BAHIAGRASS TILLER UNDER DIFFERENT NITROGEN FERTILIZER RATE AND CUTTING HEIGHT - W. Pakiding (Jurnal Ilmu dan Teknologi Peternakan, 2012)
Seasonal change of bahiagrass tiller under different nitrogen fertilizer rate and cutting height was investigated over a 4-year period. Tiller dynamics were examined using a tagging technique, with treatments of two nitrogen rates [5 g N/m2 /year (LN) and 20 g N/m2/year (HN)] x three cutting heights above ground level [20 mm (LH), 120 mm (MH) and 220 mm (HH)]. Total tiller density in the first one or two years increased in LH treatments, whereas that in MH and HH treatments decreased. Thereafter, the density reached annually constant values, showing seasonal fluctuations consisting of the spring increase and the subsequent decrease. The decrease in cutting height usually increased TAR, and the increase in nitrogen rate often increased TAR in the LH treatments. TDR increased from spring to summer and decreased thereafter. In summer and autumn, HN/LH treatment often showed higher TDR than the other treatments. The balance in LH treatments increased with increasing nitrogen rate. In the other months, the balance was usually close to zero or negative, except for LH treatments in the first year. The half-life of tillers tended to increase with decreasing nitrogen rate and cutting height. Tillers appearing in autumn survived longest, and those appearing in spring shortest. The results show that bahiagrass copes with severe management conditions by increasing its tiller longevity. This is taken as an important mechanism for the high persistence of the grass. In addition, bahiagrass tolerates severe defoliation (LH treatments) also by increasing TAR and thus tiller density